"Always looking for a new balance": toward an understanding of what it takes to continue working while being diagnosed with relapsing-remitting multiple sclerosis. Issue 21 (9th October 2018) - Meide, Hanneke van der; Gorp, Dennis van; van der Hiele, Karin; Visser, Leo
Abstract: Background: The aim of this study was to gain insight into the meaning of work in the everyday lives of people with relapsing-remitting multiple sclerosis, and the barriers and facilitators to staying in work. Methods: Nineteen employed adults diagnosed with relapsing-remitting multiple sclerosis participated in narrative interviews. All interviews were transcribed and coded for thematic analysis. Results: For people with relapsing-remitting multiple sclerosis, continuing to work was a precarious balancing act. Five themes influenced this balance: becoming familiar with the disease, adjusting expectations, having an understanding and realistic line manager, seeing work as meaningful life activity and strategic considerations. Conclusions: People receiving a diagnosis of relapsing-remitting multiple sclerosis have to refamiliarize themselves with their own body in a meaningful way to be able to continue their work. Rehabilitation professionals can support them herein by taking into account not merely functional capabilities but also identity aspects of the body. Medication that stabilizes symptoms supports making the necessary adjustments. A trusting relationship with the line manager is vital for this adaptation process. Additionally, a match between being adequately challenged by work, while still having the capacity to meet those work demands, is needed, as is long-term financial stability. Implications for rehabilitation: Rehabilitation professionals can support employees with relapsing-remitting multiple sclerosis by taking into account not merely functional capabilities but also identity aspects of the body. A trusting relationship with the line manager, including a timely disclosure of the diagnosis, is vital for people with relapsing-remitting multiple sclerosis to remain at work. For people with relapsing-remitting multiple sclerosis, there is a delicate balance between being adequately challenged by work while still having the capacity to meet work demands.